(untitled) ("Temas Sociais" Journal, 2022)
The social worker who works within the scope of judicial processes of promotion and protection, promotes difficult decisions in contexts of uncertainty, guided by different circumstances that interfere in the dynamics of their thought process and consequent decision-making. The daily practice of Social Work is, therefore, defined by the excess of procedures, based on a bureaucratic logic, imposed by organizations, which limit the execution of this professional’s work. In Portugal, we can observe the obligation of compliance with institutional guidelines and regulations, embodied in manuals of procedures, as a mandatory resource for the elaboration, namely, of social information and reports, by the Social Service. The social worker is required, following certain references, to ensure that the risk assessment and the corresponding decision process are necessarily based on rational thinking, avoiding any other type of influence on their decision-making.